Development of Sago Analog Rice with The Addition of Glucomannan Flour Using Value Engineering Method - Yanuarga Lalita Dwiutami; Suharno Suharno; Mohammad Affan Fajar Falah (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2023)
Analog rice is an imitation of rice made with non-rice ingredients such as tubers and cereals as an alternative healthy food. However, the existence of analog rice has not been fully known and accepted by the public due to a lack of knowledge. The physical characteristics of analog rice do not resemble paddy rice and still have several attributes that interfere with consumer acceptance. Adding glucomannan to make analog rice is expected to improve product attributes. This study aims to determine the priority of product development attributes and produce analog rice with the best concept through high value. The method used in this product development is value engineering, which has five steps: information, creativity, analysis, development, and recommendation steps. The best concept for analogs is rice made from sago with an additional composition of 0.07 gram glucomannan flour and 7 ml pandan essence oil. Sago analog rice with 0.07 grams of glucomannan and 7 ml pandan essence oil has 83.74% carbohydrate, 3.02% fat, 4.53% protein, 8.15% water content, and 0.55% ash content.